La inscripción con letras de bronce y otros documentos epigráficos del foro de Segobriga - Abascal Palazón, Juan Manuel; Alföldy, Géza; Cebrián Fernández, Rosario (Archivo español de arqueología, 2001)
The Roman forum of Segobriga (prov. Cuenca, Spain) was paved with limestone slabs with an inscription for bronze letters at the begining of the Principate. The text mentions the donors of the pavement and helps to understand better other inscriptions belonging to the adjacent area of the city.
Gesehen am 12.03.2024
Elektronische Reproduktion der Druckausgabe